Resistance of Reinforced Concrete Frames to Progressive Collapse at Catenary Action of Beams - V. I. Kolchunov; S. Yu. Savin (Железобетонные конструкции)
The specific properties of deformation and failure of a reinforced concrete frame are investigated under sequential realization of arch and catenary action of beams after removal of the middle row column. Numerical modeling with the use of solid- and beam-type finite element models is performed for the purposes of the study. It was found that at the failure of the column of the second row the beam of the frame above the point of column removal transform to catenary structure, as evidenced by the relative deflection 1/29.8 (179 mm). The compressed concrete at the outer face of the corner column then collapsed, followed by the complete collapse of the frame. It is shown that the results of calculation performed with the use of the frame model based on solid finite elements were visually close to the results of numerical modeling with the use of bar finite element models before the onset of catenary action of the beams. For more correct modeling of reinforced concrete frame structures when catenary action of beams is realized in them. It is advisable to use specific modeling methods, such as accounting for additional rotations of sections at crack formation.